Role of neurotoxicants in the pathogenesis of Alzheimer's disease: a mechanistic insight. (1st January 2021) - Nisa, Fatema Yasmin; Rahman, Md. Atiar; Hossen, Md. Amjad; Khan, Mohammad Forhad; Khan, Md. Asif Nadim; Majid, Mumtahina; Sultana, Farjana; Haque, Md. Areeful
Abstract: Alzheimer's disease (AD) is the most conspicuous chronic neurodegenerative syndrome, which has become a significant challenge for the global healthcare system. Multiple studies have corroborated a clear association of neurotoxicants with AD pathogenicity, such as Amyloid beta (Aβ) proteins and neurofibrillary tangles (NFTs), signalling pathway modifications, cellular stress, cognitive dysfunctions, neuronal apoptosis, neuroinflammation, epigenetic modification, and so on. This review, therefore, aimed to address several essential mechanisms and signalling cascades, including Wnt (wingless and int.) signalling pathway, autophagy, mammalian target of rapamycin (mTOR), protein kinase C (PKC) signalling cascades, cellular redox status, energy metabolism, glutamatergic neurotransmissions, immune cell stimulations (e.g. microglia, astrocytes) as well as an amyloid precursor protein (APP), presenilin-1 (PSEN1), presenilin-2 (PSEN2) and other AD-related gene expressions that have been pretentious and modulated by the various neurotoxicants. This review concluded that neurotoxicants play a momentous role in developing AD through modulating various signalling cascades. Nevertheless, comprehension of this risk agent-induced neurotoxicity is far too little. More in-depth epidemiological and systematic investigations are needed to understand the potential mechanisms better to address these neurotoxicants and improve approaches to their risk exposure that aid in AD pathogenesis. Key messages: Inevitable cascade mechanisms of how Alzheimer's Disease-related (AD-related) gene expressions are modulated by neurotoxicants have been discussed. Involvement of the neurotoxicants-induced pathways caused an extended risk of AD is explicited. Integration of cell culture, animals and population-based analysis on the clinical severity of AD is addressed.